Elucidating the role of κ-carbides in FeMnAlC alloys on abrasion wear. (July 2019) - Zambrano, O.A.; Valdés, J.; Rodriguez, L.A.; Reyes, D.; Snoeck, E.; Rodríguez, S.A.; Coronado, J.J.
Abstract: FeMnAlC alloys with high C and Al contents exhibit hardness that could be enhanced drastically with the precipitation of nano κ-carbides through aging and thermomechanical treatments. Nonetheless, information has been scarcely reported on the effect of both treatments on the abrasive wear response of those alloys. Consequently, wear tests were performed using the pin on abrasive paper configuration. The aging treatments were performed at 550 °C for 4, 8 and 15 h of aging time and thermomechanical treatments were applied using compression at temperatures from 900 °C to 1150 °C and at strain rates from 0.01 to 1 s −1 . The results showed a strong correlation between the mismatch of the κ-carbide and γ matrix with the wear coefficient. Highlights: Aging and TMT treatments increase the wear response in FeMnAlC alloys. The mismatch between κ-phase and γ has an important role on the wear behaviour. The number of micro-grooves are inversely proportional to the hardness. The FeMnAlC alloy showed higher wear resistance than conventional steels.